Cardiovascular magnetic resonance of cardiac morphology and function: impact of different strategies of contour drawing and indexing - Riffel, Johannes; André, Florian; Ochs, Marco; Hirschberg, Kristóf; Schaub, Ebe; Fritz, Thomas; Müller-Hennessen, Matthias; Giannitsis, Evangelos; Katus, Hugo; Friedrich, Matthias (Clinical research in cardiology, 2019)
BackgroundCardiovascular magnetic resonance (CMR) is the gold standard for the quantitative assessment of cardiac volumes, mass and function. There are, however, various strategies for establishing endocardial borders, the cardiac phase used for measurements and the body dimensions used for indexing these results. The aim of the study was to assess the impact of different strategies on reference values.Methods and results362 healthy volunteers (190 men, mean age 51 ± 13 years) underwent a standard CMR protocol. Left ventricular end-diastolic (LV-EDV) and end-systolic (LV-ESV) volumes and LV mass (LV-M) were measured at end systole and end diastole in SSFP sequences using two methods, one of which included papillary muscles and trabecular tissue in the LV-M (“include” approach), while the other excluded this tissue (“exclude” approach). There was a strong correlation between the results for LV volumes and LV ejection fraction (LV-EF) between the “include” and the “exclude” approach, while the mean values were different: LV-EDV: 149.7 ± 32.5 ml vs 160.5 ± 35.0 ml, p < 0.0001; LV-ESV: 48.7 ± 14.5 ml vs 56.4 ± 16.7 ml, p < 0.0001; LV-EF: 67.7 ± 5.4% vs 65.1 ± 5.6%, p < 0.0001. When comparing end-systolic with end-diastolic data, values for LV-M were significantly higher in end systole irrespective of whether papillary muscles and trabecular tissues were included or not. Furthermore, LV-M missed overweight-induced LV hypertrophy when indexed to body surface area (BSA) instead of height.ConclusionQuantitative assessment of LV volumes and mass with inclusion of papillary muscles and trabeculae to myocardial mass resulted in significantly different values, while indexing to BSA and not height may miss LV hypertrophy in terms of overweight.
Gesehen am 03.05.2019